The role of social media as a persuasive ubiquitous learning tool for social engagement towards social sustainability / Nur Azura Mahmud, Melissa Shahrom and Norshima Humaidi - Mahmud, Nur Azura; Shahrom, Melissa; Humaidi, Norshima (Faculty of Business and Management, UiTM Shah Alam, 2020)
Social media has infiltrated the 21st-century generations of Internet users, making it a very prominent means of communications dissemination, particularly among students at a higher level of education. As technology will continue to evolve the role humans play in the near future, everyone will be required to adapt their skills throughout their daily and working lives. Therefore, individuals especially younger generations will need to act and engage in lifelong learning, so they are adaptable when the changes happen. Nowadays, the learning process is not only confined to the walls of the classrooms, instead, students are also able to access knowledge at any time and place that they are comfortable with to clear their doubts. Social media has also brought forth the concept of ubiquitous learning, which means that students can explore and request a related topic of interest from experts from all around the world. While this social engagement brings many benefits to the students particularly towards improving their self-esteem and enhance their learning philosophy. However, the question of can their social media engagement behaviours affect their social sustainability is still in debate. Hence, this research will explore the role of social media as a persuasive ubiquitous learning platform to enhance individual social sustainability. The research focuses on a particular field such as in education and society and will also relate the gratification factors on how social media like LinkedIn and Twitter will broadly affect students and societies. Questionnaires will be distributed through LinkedIn, to find out whether student is impacted by social media for social sustainability or not. This paper demonstrates the ideas of social media and other aspects like the importance of social media in social engagement for social sustainability. It also presents an outline on social media LinkedIn as a tool. It helps organizations to understand why students use social media and what gratifications they receive from social media for social sustainability.